Comparison of Efficacy of Serratiopeptidase and Escin after Impacted Mandibular Third Molar Surgery: A Randomized Controlled Clinical Trial - Dahak, Arwa Mohammed Hussein Ahmed (University of Science and Technology, Sana’a, 2026)
This split-mouth, randomized controlled trial aimed to evaluate the effectiveness of serratiopeptidase and escin—each administered alongside conventional medications—in reducing postoperative complications following impacted mandibular third molar surgery. Twenty-four eligible patients were enrolled and randomly assigned to receive either oral serratiopeptidase or oral escin in addition to standard postoperative care (12 patients per group). Data were analyzed using SPSS (version 28) and JASP (version 0.18.3). The results indicated that serratiopeptidase significantly reduced postoperative pain compared to conventional treatment alone, though it had no statistically significant effect on trismus or facial edema. In contrast, escin significantly decreased both postoperative trismus and pain, while its effect on facial edema was not statistically significant. When combined with conventional therapy, neither agent demonstrated a statistically significant advantage over the other in reducing trismus, facial edema, or pain. Nonetheless, escin exhibited slightly greater effect sizes for trismus and facial edema. As the first randomized clinical trial to compare these specific agents following impacted mandibular third molar surgery, this study offers preliminary evidence and underscores the need for further research to refine clinical management strategies. Clinical Trial Registration: ClinicalTrials.gov (NCT07304882); ISRCTN registry (ISRCTN15432618).
Keywords: Serratiopeptidase; Escin; Mandibular Third Molar Surgery; Oral Surgery; Sana'a